The cults of the Roman Empire - Turcan, Robert, 1929-2018. (Malden, MA ; Oxford, UK)
xiii, 399 sayfa
Keywords: “This book is about the multiplicity of gods and religions that characterized the Roman world before Constantine. It was not the noble gods such as Jove, Apollo and Diana, who were crucial to the lives of the common people in the empire, bur gods of an altogether more earthly, earth level, whose rituals and observances may now seem bizarre. As well as being of wide general interest, this book will appeal to students of the Roman Empire and of the history of religion.” --